Food and mental health during the Covid-19 pandemic (Research, Society and Development, 2021)
The pandemic caused by Covid-19 led to isolation and social distance, loss of jobs, changes in family income, changes in eating habits, as well as difficulties in accessing food and the unpredictability that affect the physical and emotional health of individuals and collectivity. In this context, the aim was to evaluate aspects related to food and mental health of the population of Santa Catarina during the Covid-19 pandemic. Data collection was performed by remotely applying a questionnaire from December 2020 to February 2021. The questionnaire was composed of questions that addressed the sociodemographic profile, Brazilian Scale of Food Insecurity, Test – How is your diet? from the Ministry of Health, Food consumption markers form of the Food and Nutritional Surveillance System and symptoms of depression and anxiety based on the inventory of The Mind Overcoming Humor. The research was approved under Opinion No. 4,357,984. In all, 36.5% of respondents were at some level of food and nutrition insecurity. The majority (93.9%) had satisfactory eating habits during the pandemic. Regarding anxiety, it was observed that 56.2% of the participants felt worried most of the time and easily tired. As for depression, 50.7% of respondents felt tired, with loss of energy and had an alteration in their sleep pattern. It is concluded that the food of the participants is adequate, although it was found that 1/3 of the families were food insecure. Symptoms associated with anxiety and depression were found in an important percentage of the sample.